Metabolite profile of two Allium cepa L. aggregatum group cultivars by Nuclear Magnetic Resonance - Fransiska Renita Anon Basundari; Endang Sulistyaningsih; Rudi Hari Murti; Tri Rini Nuringtyas (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Basundari FRA, Sulistyaningsih E, Murti RH, Nuringtyas TR. 2021. Metabolite profile of two Allium cepa L. aggregatum group cultivars by Nuclear Magnetic Resonance. Biodiversitas 22: 3127-3135. Shallot, an Allium species with high economic value, is widely cultivated in Indonesia. The species includes numerous cultivars with unique characteristics, such as harvesting time, yield, taste, odor, and bulb color. Tuk Tuk and Trisula, the cultivars used in this experiment, have different bulb colors. Tuk Tuk’s bulb color is light red, while that of Trisula is dark red. This color difference may be attributed to variations in the metabolite contents of the shallot bulbs. The present experiment aimed to reveal differences in the metabolite contents of the two shallot cultivars by using Nuclear Magnetic Resonance (NMR) and then determine the specific metabolites contributing to these differences. Bulbs of Tuk Tuk and Trisula were planted in the field under the same conditions and then collected. The bulb samples were powdered, freeze-dried, and subjected to a two-phase extraction method with CDCl3 and D2O as solvents to separate the nonpolar metabolites from polar ones. The extracts were analyzed by 1H-NMR, and the spectra collected were analyzed using MNOVA software and Metaboanalyst.ca. A total of 23 metabolites were successfully identified and characterized in this experiment. The contents of eight of these metabolites, namely, sucrose, glutamine, citric acid, choline, methiin, propiin, threonine, and formic acid, were significantly higher in Trisula than in Tuk Tuk. These differences may be correlated with variations in the color intensity, pungency, and other traits of the cultivars. The results demonstrate that NMR metabolite profiling could effectively differentiate metabolite profile variations among shallot cultivars.